"Anorexia Wants to Kill Me, Dysphoria Wants Me to Live": Centering Transgender and Nonbinary Experiences in Eating Disorder Treatment. Issue 3 (1st August 2022) - Cusack, Claire E.; Levenson, Nitai H.; Galupo, M. Paz
Abstract: The present study focused on the lived experience of eating disorder (ED) treatment among trans and nonbinary (TNB) individuals. Forty-six participants answered open-ended prompts on how gender was incorporated into their eating disorder treatment in ways that were both helpful and unhelpful. Using thematic analysis, four themes were identified as helpful: 1) Processing Gender Dysphoria; 2) Normalizing Gender Diversity; 3) Unpacking Gender Role Expectations; and 4) Therapist Characteristics. Themes identified as unhelpful included: 1) Providers Not Knowledgeable; 2) Etiology Stereotypes; 3) (Hetero)cisnormativity; 4) Gender Not a Focus; and 5) Treatment as Gendered. Implications focus on improving the quality of ED treatment for TNB people.